Wear-out and breakdown of Ta2O5/Nb:SrTiO3 stacks. (December 2022) - Boyeras Baldomá, S.; Pazos, S.M.; Aguirre, F.L.; Ankonina, G.; Kornblum, L.; Yalon, E.; Palumbo, F.
Highlights: Main features of the breakdown Ta2 O5 /Nb:SrTiO3 stacks are presented and analyzed. Nb:SrTiO3 back electrodes provides a well-defined surface for the study of Ta2 O5 layer. Our results outline the performance limits of Ta2 O5 films for development of devices. Abstract: Tantalum oxide (Ta2 O5 ) is widely used in electronics, with important applications in backend capacitors and memristors. However, major technological challenges have to be faced and solved. Also, concerns related to the reliability of these new stacks have to be taken into consideration. We report the reliability of Ta2 O5 films focusing on the dynamics of the charge trapping and their leakage behavior under a constant voltage stress. We leverage the use of Nb:SrTiO3 back electrodes as a clean, well-defined surface, allowing the study of the Ta2 O5 layer with no significant interface effects. The main features of the breakdown Ta2 O5 /Nb:SrTiO3 stacks are presented and analyzed in terms of an electromigration-based model. Our results outline the performance limits of Ta2 O5 films, providing guidelines for development and integration of current and future devices.